Utilization of Sang Mamong Leaf Extract (Lantana camara) as an Anti-Head (Pediculus humanus capitis) Lice Shampoo - Riskayanti, Yunita; Febrianti, Mutia (Jurnal Pijar Mipa, 2025)
Head lice (Pediculus humanus capitis) are a scalp health problem that can attack all ages, especially children aged 3–11 years. Women have a higher risk of infection than men. In Seteluk District, West Sumbawa Regency, a survey of 40 children aged 6–13 years (20 girls and 20 boys) showed that 100% of girls (20 people) had head lice, while only 20% of boys (4 people) who are infected. The high risk in girls is influenced by wearing the hijab from an early age, hot weather, and sweat, which causes hair to become wet, thereby supporting the development of head lice. Head lice cause severe itching that triggers excessive scratching, potentially causing wounds, irritation, scalp infections, and increasing the risk of fever in children. This research aims to prove the effectiveness of sang mamong (Lantana camara L) leaf extract as an anti-head lice (Pediculus humanus capitis) shampoo through quantitative experimental methods. Making sang mamong extract using 60 grams of dry and fine sang mamong, using 450 mL of 96% alcohol for 2 days, then heated at 70 oC to produce sang mamong extract. Data analysis techniques are based on the results of pH measurement tests, foam height tests, and activity tests. The researcher's hair lice activity test results used 1 mL of anti-lice material, dropped evenly on filter paper, and placed in a petri dish. For anti-lice shampoo without using sang mamong leaf extract, the 3 fleas tested showed no change in active flea activity for up to 1 hour, whereas for shampoo containing sang mamong extract it showed different activity for each extract and the most effective flea activity test results were Anti-lice shampoo containing 4% sang mamong can kill 2 head lice, 1 within 4 minutes and 1 within 11 minutes, and this shows that anti-lice shampoo containing Sang mamong extract (Lantana camara L) is still better than the shampoo sold on the market, based on activity tests, market shampoo is only able to make 2 lice immobile in just 30 minutes, then 3 lice move again for up to 60 minutes without showing any change. The pH measurement test shows an average value of 6, and the foam height test produces an average value of 8.5. Based on these findings, sang mamong (Lantana camara L) leaves can produce an effective anti-head lice shampoo. Tests for pH levels, foam height, and flea activity on shampoo made from sang mamong (Lantana camara L) leaves meet the criteria for good quality shampoo. Shampoo trials have been conducted on 3 children and 2 teenagers, showing safe results without irritation. scalp and effectively makes hair lice fall out during use.